Microscopic characterization, TLC fingerprinting and determination of total phenol and flavonoid of different population of Camellia sinensis (L.) Kuntze (green tea) compared to a standard sample - Zahra Shahbazi; Mohammad M. Zarshenas; Mahmoudreza Moein; Sedigheh Khademian; Hamed Etemadfard (Shiraz University of Medical Sciences, 2019)
With respect to the importance and high consumption of this drink, assessment of various brands and populations are needed to reach to high quality samples. Low-quality or fake samples may cause many unwanted effects. Therefore, comparative study of various samples will be beneficial to select a high quality sample. This study aimed to assess evaluate the quality of fourteen green tea samples based on microscopic characterization and pharmacognostical properties. Fourteen green tea samples were purchased from markets (Iran), both internal and external brands. Also a sample was collected from Lahijan (North of Iran) as a control. The methanol extracts of all samples were subjected to microscopic characterization as well as determination of total phenol and flavonoid content using current related methods. In addition, thin layer chromatography (TLC) fingerprint was performed on all respected extracts using HPTLC technique. Microscopic characterization showed calcium oxalate crystal, trichomes, idioblasts, stroma in high quality samples. Total phenol content of Chinese teabag methanol extract was at highest (288.4±12.03 mg GAE/g extract) and the lowest phenol content was related to the Chinese bulk sample (144.76±4.32 mg GAE/g extract). On the other hand, highest and lowest flavonoid content was found in Pakistan (19.77±0.68 mg QE/ g extract) and Lahijan (4.5±0.02 mg QE/ g extract) bulk samples, respectively. TLC chromatogram fingerprint indicated the presence of phenolic compounds with related intensity. Current study represented that these assessments are well functional and beneficial to be consider for the screening and quality control evaluation of various tea samples from different origins.